2019
DOI: 10.1530/ec-18-0281
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/phenotype correlations in 538 congenital adrenal hyperplasia patients from Germany and Austria: discordances in milder genotypes and in screened versus prescreening patients

Abstract: Congenital adrenal hyperplasia (CAH) due to CYP21A2 gene mutations is associated with a variety of clinical phenotypes (salt wasting, SW; simple virilizing, SV; nonclassical, NC) depending on residual 21-hydroxylase activity. Phenotypes and genotypes correlate well in 80–90% of cases. We set out to test the predictive value of CAH phenotype assignment based on genotype classification in a large multicenter cohort. A retrospective evaluation of genetic data from 538 CAH patients (195 screened) collected from 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 31 publications
4
35
0
2
Order By: Relevance
“…In our cohort, we found a high correlation between genotype and phenotype, similarly to a report on a large cohort from Brazil 18 . However, other authors reported higher percentages of discrepancy 17,33,37‐39 …”
Section: Discussionsupporting
confidence: 92%
“…In our cohort, we found a high correlation between genotype and phenotype, similarly to a report on a large cohort from Brazil 18 . However, other authors reported higher percentages of discrepancy 17,33,37‐39 …”
Section: Discussionsupporting
confidence: 92%
“…7 Medical Office, Endokrinologikum, Ulm, Germany. 8 Paediatric Endocrinology, University Children's Hospital, Munich, Germany. 9 Paediatric Endocrinology, University Children's Hospital, Freiburg, Germany.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The phenotype is influenced by the activity of the less affected allele, and the residual activity of 21-hydroxylase in the patients is around 20-50% [7]. However, the phenotypical degree of severity within a genotype can vary greatly and different phenotypes can be associated with the same mutation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the phenotype is extremely variable [63,64] since the majority (>65%) of CAH patients are compound heterozygotes with one or more mutations in both CYP21A2 alleles [64,65,66,67,68,69]. In these cases, the clinical phenotype depends on the less severely affected allele [53] (Figure 3B).…”
Section: 21-hydroxylase Deficiency (21-ohd)mentioning
confidence: 99%